DISASTER MANAGEMENT AS A COMPONENT IN SCHOOL CURRICULUM - Kaur, Gurkirat (SCHOOL SCIENCE, 2010)
Disaster is a sudden adverse or unfortunate extreme event resulting in loss of lives and properties. Disaster management is preparing for reacting and recovering from disasters. In India, it has been introduced at school level and preparing children to combat and sensitise about disasters, will prove a fruitful and blessing for millions of lives saved by them .